2020
DOI: 10.2196/19538
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Issues and Lessons Learned From COVID-19 Clinical Trials With Lopinavir-Ritonavir and Remdesivir

Abstract: Background Recently, three randomized clinical trials on coronavirus disease (COVID-19) treatments were completed: one for lopinavir-ritonavir and two for remdesivir. One trial reported that remdesivir was superior to placebo in shortening the time to recovery, while the other two showed no benefit of the treatment under investigation. Objective Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…The question regarding the usage of Ritonavir in the treatment in COVID-19 is an important one that requires further studies. [ 36 ] Clinical trials are being conducted on experimental treatments. Some, like hydroxychloroquine and lopinavir/ritonavir, were expected to be successful early in the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The question regarding the usage of Ritonavir in the treatment in COVID-19 is an important one that requires further studies. [ 36 ] Clinical trials are being conducted on experimental treatments. Some, like hydroxychloroquine and lopinavir/ritonavir, were expected to be successful early in the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ultimate outcomes of many discharged patients cannot be determined from the primary hospital’s medical records. Wolkewitz et al and Yi et al [ 1 , 2 ] discussed different types of bias that may occur when analyzing in-hospital COVID-19 data.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the analytic approach, informative censoring may lead to biased survival estimates [ 3 , 4 ]. An increasing awareness of this issue appears in a variety of medical literature involving patients with COVID-19 [ 1 , 2 ], surgical site infections [ 5 ], kidney transplants [ 6 ], and cancer [ 7 ]. Simulation studies demonstrate that the magnitude of the bias depends on the hazard ratio of the treatment effect and the proportion of patients who are informatively censored [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various mutants have appeared one after another [ 3 , 4 ], which makes epidemic prevention and control more difficult. Although some studies have shown that several drugs can improve the clinical symptoms of COVID-19 [ 5 ], the efficacy of their treatment is controversial [ 6 ]. The main protective measures currently in place are vaccinations, masks, and isolation.…”
Section: Introductionmentioning
confidence: 99%